Effect of meal frequency and timing on physical performance - Hawley, J. A.; Burke, L. M. (British Journal of Nutrition, 1997)
Two areas of sports nutrition in which the periodicity of eating has been studied relate to: (1) the habitually high energy intakes of many athletes, and (2) the optimization of carbohydrate (CHO) availability to enhance performance. The present paper examines how the timing and frequency of food and fluid intake can assist the athlete and physically-active person to improve their exercise performance in these areas. Frequent eating occasions provide a practical strategy allowing athletes to increase energy intake while concomitantly reducing the gastric discomfort of infrequent large meals. The optimization of CHO stores is a special challenge for athletes undertaking prolonged training or competition sessions. This is a cyclical process with post-exercise CHO ingestion promoting muscle and liver glycogen re-synthesis; pre-exercise feedings being practised to optimize substrate availability and feedings during exercise providing a readily-available source of exogenous fuel as endogenous stores become depleted. The timing and frequency of CHO intake at these various stages are crucial determinants for optimizing fuel availability to enhance exercise capacity.